DNA methylome analysis identifies BMI‐related epigenetic changes associated with non‐small cell lung cancer susceptibility. (3rd May 2021) - Li, Guyanan; Meng, Hua; Bai, Yansen; Wei, Wei; Feng, Yue; Li, Mengying; Li, Hang; He, Meian; Zhang, Xiaomin; Wei, Sheng; Li, Yangkai; Guo, Huan
Abstract: Background: Body mass index (BMI) has been reported to be inversely associated with incident risk of non‐small cell lung cancer (NSCLC). However, the underlying mechanism is still unclear. This study aimed to investigate the role of DNA methylation in the relationship between BMI and NSCLC. Methods: We carried out a genome‐wide DNA methylation study of BMI in peripheral blood among 2266 Chinese participants by using Illumina Methylation arrays. For the BMI‐related DNA methylation changes, their associations with NSCLC risk were further analyzed and their mediation effects on BMI‐NSCLC association were also evaluated. Results: The methylation levels of four CpGs (cg12593793, cg17061862, cg11024682, and cg06500161, annotated to LMNA, ZNF143, SREBF1, and ABCG1, respectively) were found to be significantly associated with BMI. Methylation levels of cg12593793, cg11024682, and cg06500161 were observed to be inversely associated with NSCLC risk [OR (95%CI) =0.22 (0.16, 0.31), 0.39 (0.30, 0.50), and 0.66 (0.53, 0.82), respectively]. Additionally, cg11024682 in SREBF1 and cg06500161 in ABCG1 mediated 45.3% and 19.5% of the association between BMI and decreased NSCLC risk, respectively. Conclusions: In this study, we identified four DNA methylation sites associated with BMI in the Chinese populations at the genome‐wide significant level. We also found that the BMI‐related methylations of SREBF1 and ABCG1 could mediate about a quintile‐to‐half of the effect of BMI on reduced NSCLC risk, which adds a potential mechanism underlying this association. Abstract : We identified four BMI‐related CpGs (located at LMNA, ZNF143, SREBF1, and ABCG1 ) in Chinese populations. The methylation levels of three CpGs (located at LMNA, SREBF1, and ABCG1 ) in whole blood were inversely associated with lung cancer risk. The cg11024682 and cg06500161 annotated to SREBF1 and ABCG1 genes, could mediate the associations of BMI and lung cancer risk.